A uniform gene and chromosome nomenclature system for oat (Avena spp.) - Jellen, Eric N.; Wight, Charlene P.; Spannagl, Manuel; Blake, Victoria C.; Chong, James; Herrmann, Matthias H.; Howarth, Catherine J.; Huang, Yung Fen; Juqing, Jia; Katsiotis, Andreas; Langdon, Tim; Li, Chengdao; et al. (My University, 2024)
Context. Several high-quality reference genomes for oat (Avena sativa L. and relatives) have been published, with the prospect of many additional whole-genome assemblies emerging in the near future. Aims. This has necessitated an effort by the International Oat Nomenclature Committee (IONC; all co-authors on this paper) to devise a universal system for naming oat genomes and subgenomes, chromosomes, genes, gene models and quantitative trait loci. Methods. We evaluated existing naming practices, recent data from oat whole-genome sequencing, and the newly published convention for wheat nomenclature. Key results. A framework for these rules has been posted on the GrainGenes database website (https://wheat.pw.usda.gov/GG3/oatnomenclature). The gene naming convention requires adoption of a numerical identifier for each genotype; we propose that these identifiers be assigned by contacting the GrainGenes curators, the curator of the Oat Newsletter, or a member of the IONC (as listed at the GrainGenes link above). Conclusions. We encourage oat researchers to refer to these resources, policies, procedures and conventions, adopting them as an international nomenclature standard. Implications. Adoption of these standards will facilitate communication and dissemination of oat research and allow programmatic access and data sharing across platforms, and will contribute to oat breeding and research worldwide.
Keywords: Avena; chromosome nomenclature; data standardisation; gene nomenclature; genome nomenclature; oat; plant breeding; QTL nomenclature